Molecular biology of the cell - Dolomatov, Sergey; Ageeva, Elizaveta; Zukow, Walery (Journal of Education, Health and Sport, 2022)
The book is intended for students studying medical and biological specialties. CHAPTER I. EPIGENETICS INTRODUCTION The science of epigenetics looks at the mechanisms of molecular modifications of histones and DNA that can regulate gene activity without affecting the nucleotide sequences in the DNA molecule. Recognized epigenetic regulators are DNA methylation, post-translational modifications of histones, and non-coding RNAs (nkRNAs). One of the most important differences between eukaryotic cells and prokaryotes is the presence of a complex nucleo-protein chromatin complex in eukaryotes. It is in this form that the DNA molecule is stored in our cells. On the one hand, the complex structural organization of chromatin provides a compact arrangement of DNA in the cell nucleus. On the other hand, chromatin is directly involved in the process of regulating gene expression. At the same time, the nucleosome depicted in Fig. 1 (a structural and functional unit of chromatin) is considered as a key component in the processes of regulating gene expression. The nucleus of the nucleosome is 8 histone proteins (octamers). The nucleus of the nucleosome consists of two copies of each of the histone proteins H2A, H2B, H3 and H4. The DNA chain, which includes 147 nucleotides, folds 1.65 times around the octamer of histones. The nucleosomes are arranged as a linear array along the DNA molecule in the form of "beads on a string". The linker section of DNA connecting adjacent nucleosomes (transcriptionally inactive) is sealed with H1-histone protein. The length of the linker section is 30 nm. Moreover, the site of the beginning of transcription is usually located inside the nucleosome. Consequently, the nucleosome serves as a gene repressor, preventing the initiation of transcription. That is, chromatin provides a total repression of genes. In contrast, transcription becomes possible as a result of chromatin remodeling factors that enable the "dismantling" of nucleosomes or otherwise alter their structure and organization. Thus, the repression (inactivation) of genes begins with wrapping the DNA molecule around the histones in the nucleosome, and the liberation of genes from repression (activation) involves freeing DNA from binding to histone proteins and unfolding DNA by chromatin remodeling factors (Lorch Y., Kornberg R. D., 2017). Thanks to this mechanism, selective expression of only those genes that are needed at a given time by the cell or tissue is possible. It should be emphasized that nucleosome repression extends not only to transcription, but also to most other biological processes associated with the DNA molecule, such as replication, mitotic division, repair of double-strand breaks, and maintenance of telomeres. Thus, epigenetic mechanisms control various physiological and pathological processes by regulating the expression of the corresponding genes by changing the availability of epigenetic control systems to chromatin. The scope of application of epigenetic research methods is rapidly expanding. Currently, we are witnessing the active introduction of epigenetic approaches in the field of practical medicine aimed at diagnosing and treating dangerous human diseases. CHAPTER II. TRANSCRIPTION FACTORS INTRODUCTION For the first time, the existence of transcription factors was revealed on the basis of a discovery that made it possible to establish in vitro purified RNA polymerase-II can initiate transcription on the DNA template in the presence of a cell extract (Weil P. A. et al., 1979). Further research aimed at the fractionation and identification of the general transcription factors (GTF) required to initiate transcription in vitro has identified similar factors in rats, Drosophila, and yeast and substantiated the assumption that GTFs are indeed "common" factors necessary for the expression of genes transcribed by RNA polymerase II. is highly conserved in a number of eukaryotic organisms (Matsui T. et al., 1980). We only mention RNA polymerase II because only this type of enzyme has the ability to synthesize mRNA. Whereas RNA polymerase I is responsible for the synthesis of pro-rRNA, and RNA polymerase III is responsible for the synthesis of tRNA and other non-coding cell RNAs. Meanwhile, the regulation of transcription in eukaryotes is quite complex, since it depends on chromatin remodeling complexes (Burns L. G., Peterson C. L., 1997) and covalent modification of histone proteins (Natsume-Kitatani Y., Mamitsuka H., 2016). In transcription initiation, the immediate target of GTF is a well-defined promo zone of a structural gene. In the structure of the promotra of eukaryotes, the main elements and regulatory elements can be distinguished. The main elements of the promotra (bark promoter, see Fig. 2.1) can be attributed to the site for assembling the transcription initiation complex (PIC), including the TATA sequence located above from the transcription start site (TSS ), and an initiating sequence (Inr) covering the start site. Promoters may include a TATA unit, an initiator sequence (Inr), or both (Hampsey M., 1998). A third major element, the downstream promoter element (DPE), was originally described in Drosophila and is located about 30 p.p. below TSS. The DPE promoter element appears to function in conjunction with the Inr element as a binding site for the transcription factor TFIID on non-TATA promoters. According to current research, the cellular (main) promoters of multicellular organisms that control the initiation of transcription by RNA polymerase II may contain short sequences of nucleotides called cow promoter elements (motifs) (e.g., the TATA block, the initiator (Inr), and the lower element of the cow promoter (DPE)) that recruit RNA polymerase II through a common transcription initiation mechanism (Dreos R. et al., 2021). The authors report that the classes of Promoters of Inr+DPE are not only present in the genome of Drosophila and humans and are structurally similar to each other, but may also be common to different species of multicellular organisms. The most studied element of the cow promoter is the TATA box, but the TATA box is found only in about 10-20% of multicellular cortical promoters. Therefore, along with the TATA sequence, it is necessary to name other possible key DNA sequences known as cortical promoter elements, which include: BRE, MTE, TST and DPE sequences. The two BRE (TFIIB recognition element) motifs are located either above (BREu) or below (BREd) elements of the TATA box. It should be emphasized that TBP, TATA box, and BRE demonstrate high levels of conservatism in the range from archaebacteria to humans (Kadonaga J. T., 2012). In doing so, BREu as well as BREd have both positive and negative effects on transcription activity. The downstream core promoter element (DPE) was detected in the analysis of non-TATA gene promoters in Drosophila. The MTE element (motif ten element), which is located directly in front of the DPE, was identified as an overrepresented sequence of a cow promoter called "motif 10" and then discovered, that it is a functional element of a cow promoter. The MTE and DPE motifs exhibit high conservatism in the range from Drosophila to humans, and both motifs appear to be directly recognized by the subunits of the main transcription factor TFIID, TAF proteins that resemble histone proteins in structure. In turn, the TCT sequence regulates the transcription of ribosomal protein genes in Drosophila and humans. Although there are no universal cortical promoter elements that are present in all promoters, the concept of a cow promoter of nuclear RNA polymerase II can be defined as a minimum stretch of DNA that is sufficient to accurately initiate transcription by RNA polymerase II (Kadonaga J. T., 2012; Haberle V., Stark A., 2018). It should be noted that the results of modern research will constantly supplement the list of all new components of the cow promoter, for example, DNA-replicatedrelated element (DRE), Ohler 1,6 and 7 motifs (Danino Y. M. et al., 2015; Haberle V., Stark A., 2018). According to the authors, the bark promoter may be transformed in the course of evolution. Due to this, gene expression levels can be modulated by the composition of cow promoter elements. Such modulation is directly achieved through the emergence of combinations of new elements of the cow promoter, as a result of which an additional level of transcription regulation is realized. To summarize the above facts, transcription is usually initiated at a specific position, the Transcription Initiation Site (TSS), at the 5’ end of the gene. The TSS site is embedded in a bark promoter, which is a short sequence spanning 50 base pairs above and 50 below TSS. The cortical promoter serves as a binding platform for the components required to initiate transcription, including RNA polymerase II and related common transcription factors (GTFs). Regulatory elements. The cortical promoter is sufficient to initiate transcription, but such transcription has low basal activity, which can be further activated, generally by more distally arranged regulatory elements called enhancers (discussed below). Enhancers bind regulatory proteins known as transcription factors, recruit transcription cofactors, and can further enhance transcription. CHAPTER III. CELL SIGNALING PATHWAYS INTRODUCTION In a multicellular organism, the work of each cell is regulated by a large number of signals. These signals can be formed both in the organism itself, reflecting the specific needs of a living organism (metabolic state, stages of development, differentiation, reproduction), and in the form of a reaction to the effects of the external environment. The implementation of each of these signals encompasses all the biological and biochemical processes that lead from the cell’s perception of the signal to the cell’s response. A signal to a cell is something that is recognized by a specific receptor, which in turn can initiate a response to that signal. A receptor is a structure that recognizes a signal, interprets the specificity of a signal, and translates it into the cell in the form of intracellular signaling molecules, a cascade of protein phosphorylation, and other pathways. Thus, signaling to the cell begins as soon as the signaling molecule (ligand) binds to its receptor – a protein with a complementary structure on the transmembrane protein or inside the cell. Growth factors, hormones, cytokines, neurotransmitters, components of the extracellular matrix, etc. The chemical nature of the ligands is diverse, including small molecules such as lipids (prostaglandins, steroid hormones), proteins (for example, peptide hormones, cytokines and chemokines, growth factors)., complex polymers of sugars (for example, β-glucan and zymosan) and their combinations (for example, proteoglycans), nucleic acids, etc. Binding of the ligand induces conformational changes in the receptor and is then translated into the cell by activating cascades of secondary messengers (kinases, phosphatases, GTPases, ions and small molecules such as cAMP, cGMP, diacylglycerol, etc.). Thus, the message is transmitted from the membrane to the nucleus, where the processes of gene expression, subsequent translation and targeting of the protein to the cell membrane and other organelles are triggered. There are two main types of receptors – membrane (transmembrane) cell receptors and intracellular receptors. Membrane receptors are located on the plasma membrane and have a separate extracellular domain binding ligand, a transmembrane domain that is hydrophobic in nature, and a cytoplasmic domain. Cell surface receptors can be divided into G-protein-bound receptors, tyrosine kinase-bound receptors, and ionotropic receptors. When the ligand binds, plasma receptors undergo conformational changes in their extracellular domain and activate enzymatic mechanisms associated with the cytoplasmic domain, usually kinases, phosphatases and adapter proteins. These proteins can be covalently bound to the receptor and are capable of producing secondary messengers for subsequent signal transmission. Intracellular receptors can be nuclear receptors (estrogen receptor, glucocorticoid receptor, progesterone receptor, retinoic acid receptor, thyroid hormone receptor, etc.), cytoplasmic receptors or receptors located on the membranes of organelles (mitochondria, endoplasmic reticulum and Golgi apparatus). Thus, information (ligand) received on the cell surface (e.g., through a membrane receptor) is transformed by specific enzyme systems associated with the plasma membrane receptor and transmitted in the form of secondary messengers to intracellular targets. All of these components form the path of signal transmission to the cell. However, a certain set of effector proteins, enzymes and substrates that implement cellular signals form this signaling pathway (signaling cascade). Recently, however, there has been growing evidence that not only the signaling proteins themselves play an extremely important role in the regulation of cellular signaling, but also the so-called scaffold proteins ("platform proteins", adaptor proteins), which coordinate the assembly of multicomponent protein complexes. Scaffold proteins can bind several elements of one signaling pathway into a single complex, thereby modulating the efficiency of transmission of the corresponding signal. Binding and by bringing two or more signaling proteins closer together, these platform proteins direct the flow of information in the cell, activating, coordinating and regulating signaling events in regulatory networks (Skovorodnikova P.A. et al., 2017). According to the literature, several types of scaffold proteins have been described, which cover a wide range of functions. This group of proteins is usually divided into three main categories (Fig. 1): simple proteins that bind two functionally dependent proteins (adaptors), larger multi-domain proteins designed to bind a large number of proteins and regulate their activity by complex mechanisms (scaffold⁄anchoring proteins) and proteins specialized for initiating signaling cascades by localizing certain proteins-components of signaling pathways on the cell membrane (docking proteins) ( Buday L., Tompa P, 2010) The presence of such protein platforms increases the efficiency and selectivity of the signaling pathway, and also allows the formation of regulatory feedback. e ultimate target of cell signaling pathways are transcription factors that regulate gene expression and ultimately allow the resulting signal to be converted into a change in cellular activity (Brivanlou A. H., Darnell J. E., 2002). Most signaling pathways initiate a cascade of several intracellular signaling molecules that eventually form activation proteins or transcription repressors designed to bind to a specific DNA sequence. Eukaryotic transcription factors, like other proteins, are transcribed in the nucleus, but then their translation takes place in the cytoplasm. Signal transmission to the cell is a multifactorial system, which is based on nodular complexes of special proteins of signaling cascades. However, none of the signaling pathways in the cells work in isolation. The interaction of signaling mechanisms is inevitable in complex complexes, when the system perceives a combination of stimuli (hormones, cytokines, growth factors and pathogenic ligands), but at the same time preserves the accuracy of signal transmission (Saini N., Sarin A., 2021). It is well known that a relatively small number of signaling pathways control the development of all cell types in mammals (Brivanlou A. H., Darnell J. E., 2002). Combinations and time of action of the main signaling pathways determine decisions about the fate of the cell, including events such as cell differentiation in the process of ontogenesis (Li R., Elowitz M.V., 2019; de Roo J. J. D., Staal F. J. T., 2020) and cell malignancy (Dreesen O., Brivanlou A.N., 2007; Skovorodnikova P.A. et al., 2017). Consider some of the cell signaling pathways that are most important medically important. CHAPTER IV. MOLECULAR BIOLOGY OF THE TUMOR: MECHANISMS OF INITIATION, PROMOTION AND PROGRESSION INTRODUCTION Tumor diseases occupy a leading place, both in terms of morbidity and mortality. However, despite the advances in the study of molecular genetic patterns, many unresolved questions remain. On the one hand, the spectrum of molecular markers makes it possible to diagnose, predict the course, degree of malignancy, rate of tumor progression and predict a possible response to the therapy. On the other hand, those processes that occur at the molecular level are not characterized by stability, they are dynamic and are associated with a change in the genetic profile - the appearance of many clones of tumor cells with a different set of properties. The heterogeneity of tumor diseases simultaneously complicates the strategy of managing such patients, creating the prerequisites for further study of the molecular genetic characteristics of tumor cells.